The COVID-19 pandemic influenced the temporal dynamics of antimicrobial resistance markers and bacterial community across urban wastewater treatment plants - Celso G. B. Filho; Francisca A. S. Oliveira; Victor L. M. Rodrigues; Denise C. Hissa; Maisa V. H. Barros; Allysson A. de Farias; Gabriel T. Dantas; André B. dos Santos; Julio C. M. Ximenes; Vânia M. M. Melo (Brazilian Journal of Microbiology, 2026)
Urban wastewater systems represent important interfaces between human activity and the environmental occurrence of antimicrobial resistance (AMR) markers. We assessed the temporal dynamics of intI1 , ermB , and the 16 S rRNA gene by quantitative PCR across three wastewater systems (EPC, CJC, and JW) in Fortaleza, Brazil, from November 2021 to November 2023. Bacterial communities were additionally characterized by 16 S rRNA gene metabarcoding in 18 samples collected in December 2021 and January 2022. A synchronized decline in 16 S rRNA gene and intI1 concentrations beginning in late 2022 was observed across all three wastewater systems, suggesting a shift toward lower microbial abundance. The ermB gene showed higher and more variable concentrations during part of the pandemic period, followed by convergence toward lower levels; however, the absence of antimicrobial-consumption data precluded attribution of this pattern to changes in macrolide selective pressure. Normalized antimicrobial resistance marker abundances were comparatively stable at EPC and JW but more variable at CJC. EPC exhibited the highest ASV richness, whereas CJC and JW showed greater diversity according to Shannon and inverse Simpson indices. Beta-diversity analyses identified wastewater system as the principal factor associated with bacterial community structure, while the effect of sampling period was smaller and metric-dependent. Neither ermB nor intI1 was individually associated with community composition, although intI1 showed a limited effect after adjustment for wastewater system in one model. Physicochemical parameters were not significantly associated with normalized marker abundances in the exploratory paired analysis. Arcobacter , Acinetobacter , and other potentially relevant genera were detected, but no direct associations between these taxa and the monitored AMR markers could be established. These findings highlight the value of integrating longitudinal qPCR, microbiome profiling, and environmental characterization to improve the interpretation of targeted AMR markers in One Health wastewater surveillance.

Defense-related proteins in Canavalia seeds: Implications for resistance to cowpea weevil Callosobruchus maculatus (F.) - Aline da Gama Melila Licurgo; Sarah Rodrigues Ferreira; Kayan Eudorico Ventury; Roberta Pena da Paschoa; Vanildo Silveira; Thaynã Amanda Melo Souza; Valdirene Moreira Gomes; Antonio Jesus Dorighetto Cogo; Eduardo Atem de Carvalho; Kátia V. Sales Fernandes; Antônia Elenir Amâncio Oliveira (Journal of Stored Products Research, 2026)

Land-surface wetness, greenness, and built-up intensity as modifiers of heat-related mortality in Brazil - Weeberb J. Requia; João Pedro Rodrigues Pêgo; Salil V. Deo (Environmental Research, 2026)

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

Enhanced antibiotic removal in anaerobic hybrid reactors under hydraulic stress: Insights from granular activated carbon and polyurethane foam - Thiago V.R. Soeira; Matheus N. Araujo; Elias G.F. Rezende; Caroline V. Rodrigues; Elis W. Nogueira; Marta Lois; Jesús L. Romalde; Márcia H.R.Z. Damianovic (Journal of Water Process Engineering, 2026)

Texturally targeted multi-isotopic dating of ductile deformation: the Clarke River Shear Zone, northeastern Australia - Raiza T. Rodrigues; Bruno V. Ribeiro; Gideon Rosenbaum; Fred Jourdan; Teresa Ubide; Kai Rankenburg (Journal of Structural Geology, 2026)

Assessment of the level of compliance with good agricultural practices for cotton production in the different cotton-growing zones of Benin - O'’Neil G.M.M. Takpa; Pierre G. Tovihoudji; Romain Loison; Isidore Amonmidé; Benjamin Heuclin; Emmanuel Sèkloka; Pablo Tittonell; Rodrigue V. Cao Diogo (Agricultural Systems, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Driver-specific deforestation as a modifier of wildfire PM2.5–mortality associations in Brazil - Weeberb J. Requia; Erick Frederico Kill; João Pedro Rodrigues Pêgo; Salil V. Deo; Ronan Adler Tavella; Simone Georges El Khouri Miraglia (Environmental Pollution, 2026)

Assessment of Eucalyptus seedlings grown in biodegradable containers and their growth in clonal plantations - Vitor S. Brito; Emanuela F. Gama-Rodrigues; José L. M. Gonçalves; Alexandre V. Ferraz; José C. A. Júnior (New Forests, 2026)

Intrinsic constraints on budding in the deep-sea coral Dendrophyllia cf. horsti from the Red Sea - Eleonora Re; Federica Barreca; Tullia I. Terraneo; Francesca Benzoni; Domingo A. Lattanzi Sanchez; M. Rodrigue; V. Pieribone; M. Qurban; Carlos M. Duarte (Marine Biology, 2026)
Colonial corals display diverse growth forms shaped by both environmental conditions and intrinsic developmental mechanisms. Understanding these internal morphogenetic rules is critical for accurately modeling coral colony formation. In this study, we investigated the intrinsic budding patterns of Dendrophyllia cf. horsti , an azooxanthellate deep-sea coral from the Red Sea. Using detailed morphological analyses of colony architecture, we identified consistent intrinsic constraints that govern colony development. Lateral corallites bud at a consistent angle (mean 15.9°) relative to the growth axis, and the orientation of the directive septa in daughter corallites remains stable across generations (mean 19.8°). Budding was consistently restricted to two specific sites per internode located near the lateral primary septa. In most colonies, budding occurred on the same side at successive internodes, although occasional observations suggested variation in the relative position of budding sites. These findings suggest that even in deep-sea, non-photosynthetic species, colony morphology is strongly regulated by intrinsic developmental constraints, as previously demonstrated in congeneric species. The results contribute valuable data for simulating coral growth and highlight the importance of intrinsic constraints in shaping colonial forms across Scleractinia.

Ecotoxicity assessment of dairy wastewater: environmental risks and regulatory needs - Magno Lange Albuquerque; Fernando Rodrigues-Silva; Alyson Rogério Ribeiro; Carollina M. Chávez; Gilcinéa de Cássia Santana; Alessandra da S. Martins; Camila C. Amorim; Maria Clara V. M. Starling (Ecotoxicology, 2026)

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

A sustainable approach for the functionalization of lyocell nonwovens by hardwood kraft lignin - Marta A. Teixeira; Fábio Bernardo; Lúcia Rodrigues; Pedro Loureiro; Carla J. Silva; Dmitry V. Evtuguin (Journal of Cleaner Production, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Root-zone Application of Biochar and Compost Improves Maize Crop Performance, Nutrient Use Efficiency and Profitability Under Sub-humid Tropical Climate - Waliou A. Abiola; Pierre G. Tovihoudji; Rodrigue V. C. Diogo (Journal of Soil Science and Plant Nutrition, 2026)

Traditional Chinese medicine techniques for the management of fibromyalgia: a systematic review of randomized controlled trials - Helena L. Silva; Andreia V. Santos; Alexandra B. Monteiro; Maria R. Sousa; Jorge Magalhães Rodrigues (Advances in Traditional Medicine, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

The emergence of pathogens on fish in an impacted estuary and the role of non‐native piranhas in a potential bacterial infectious outbreak - Ryan Andrades; Helder C. Guabiroba; Kathiani V. Bastos; Vítor L. A. Rodrigues; Marcelo R. D. Santos; Clarisse M. Arpini; Mayra Cunha Flecher; Helen A. Pichler; Ciro C. Vilar; Maurício Hostim‐Silva; Jean‐Christophe Joyeux (Journal of Fish Biology, 2026)
As many tropical aquatic ecosystems worldwide, the Doce River estuary (DRE, southeastern Brazil) has increasingly faced multiple anthropogenic threats, including deforestation, mining, species introduction and water management. The 2015 collapse of the Fundão iron ore tailings dam severely changed water properties and increased heavy metal concentration in sediment. However, the potential synergistic effects of the observed threats on fish populations remain largely unknown. After detecting an elevated number of fin lesions in DRE fishes, we used the catfish Genidens genidens (Cuvier, 1829) to investigate whether such mutilations originated from fin‐nipping by non‐native piranha or emerged as a result of fin rot disease through bacterial infection. One third of the examined individuals had fin lesions in the DRE, whereas no conspecific exhibited such lesions in two control estuaries where piranhas are absent; lesions were restricted to the caudal fin, a region known to be targeted by fin‐nipping piranhas. Independently of the presence of fin lesion, culture of fins and livers indicated higher prevalence and variety of bacterial strains in DRE individuals than in a control area. Piranhas likely contribute to the fin lesions in DRE fishes. However, the higher prevalence and variety of bacterial pathogens as well as of liver and kidney disorders identified in fin‐healthy and mutilated fishes of the DRE suggest that the heavily metal‐polluted conditions in the DRE may be associated with the emergence of bacterial infections in fish.

American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.

Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Tamaeh Monteiro-Alfredo; Camila de O. Gutierrez; Claudiane V. Almeida; Vinicius C. da Silva; Patrícia Gomes; Caio F. R. de Oliveira; Elisângela S. Madalozzo; Edson Crusca; Raquel M. Q. Orozco; Lucas Lima; Marlon H. Cardoso; Octávio L. Franco; et al. (Probiotics and Antimicrobial Proteins, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Cu(I)-N-Heterocyclic carbenes as potent inhibitors of SARS-CoV-2 replication - Igor Andrade Santos; Josielle V. Fontes; Gustavo C. Rodrigues; Mariana Ortiz de Godoy; Glaucius Oliva; Rafael V. C. Guido; Andres Merits; Camilla Abbehausen; Mark Harris; Ana Carolina Gomes Jardim (BioMetals, 2026)

Implications of agroecological transition on performance and soil carbon inputs in farms from highly productive cashew zones of Benin - Bernus Z. Djigbe; Pierrot Lionel Yemadje; Verónica El Mujtar; Rodrigue V. Cao Diogo (Agricultural Systems, 2026)

Quantification and characterization of collagen in experimentally induced wounds treated with different types of platelet-rich plasma gel - G. Haro de Melo; F. M. Moreira; G. G. Mori; L. F. Bento; D. V. Barrionuevo; C. B. Laposy; R. Giuffrida; A. F. F. Rodrigues; G. A. T. Ozaki; D. A. F. da Silva; F. L. Pacagnelli; R. M. B. Nogueira (Cell and Tissue Banking, 2026)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests ( p < 0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP ( p = 0.009) and heterologous PRP ( p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group ( p = 0.028) in relation to the control, but, on average ( p < 0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous when compared to heterologous and homologous PRP treatments.

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Synthetic cannabinoids in hair: a review of recent findings and analytical methods by LC-MS/MS - Rafaela S. Pereira; Olívia B.O. Moreira; Marcone Augusto L. de Oliveira; Claudiane C. Canuto; Diogo O.C. Lemos; Lucas M. Duarte; Silvana V. Rodrigues (Analytica Chimica Acta, 2026)

IMTA Production of Pacific White Shrimp Integrated with Mullet, Sea Cucumber, Oyster, and Salicornia in a Biofloc System - Enrique A. Estévez Hernández; Ivanilson Santos; Laura Moraes; Morena Salala Kashane; Marcelo H. Okamoto; Luís André Sampaio; Dariano Krummenauer; César S. B. Costa; Ricardo V. Rodrigues; Silvia Martínez-Llorens; Luís H. Poersch (Fishes, 2026)
Integrated multitrophic aquaculture (IMTA) emerges as a sustainable strategy to control the excess of solids and inorganic nutrients that tend to increase in the biofloc system (BFT) cycle, since the model integrates organisms from different trophic levels sharing the same system and nutrients. Thus, this study compared a Penaeus vannamei monoculture system with an integrated biofloc system including Mugil liza, Holothuria grisea, Crassostrea tulipa, and Salicornia neei, focusing on water quality and the performance of organisms and systems. This study consisted of three monoculture systems (16 m3; 375 shrimp m−3) and three IMTA systems, composed of a shrimp tank (16 m3), a mullet tank (4 m3; 30 ind m−3), a combined tank (3 m3) for oysters (45 ind m−3) and sea cucumbers (3 ind m−2), and a Salicornia neei bed (2.78 m2; 37 ind m−2). All IMTA systems operated in recirculation without water exchange, using 10% of the established biofloc inoculum. The IMTA system had half the hydrated lime use (2.13 vs. 4.29 kg), lower solids (299.56 vs. 373.33 mg L−1), and reduced sludge production (9.37 vs. 15.87 kg). Shrimp growth was similar in both systems. Mullet grew adequately with a survival rate of 95.8%, but oysters showed a survival rate of 45.7%. Sea cucumber had a survival rate of 100% until day 28, when a marked decline appeared, strongly correlated with rising temperature (>28 °C; r = −0.71). This resulted in a significant increase in solids in the last weeks, suggesting that the population decline reduces solids control capacity. Furthermore, the biofloc in IMTA was dominated by coccoid forms, with lower proportions of filamentous and cyanobacterial forms.

Application of a Liquid Chromatography: Tandem Mass Spectrometry Based Method to Determine Plasma Cycloserine Concentrations in Indian MDR-TB Patients—A Pilot Study - Rohan V. Lokhande; Prerna R. Arora; Camilla Rodrigues; Ganesh R. Bhagure; Zarir F. Udwadia; Amita Gupta; Jeffrey A. Tornheim; Tester F. Ashavaid; Lancelot M. Pinto; Jai B. Mullerpattan; Ayesha Sunavala; Jigneshkumar Patel; et al. (Indian Journal of Clinical Biochemistry, 2026)

Biomonitoring of microplastics in the Caribbean Sea with invasive lionfish - Sahara M. Ríos-Bonilla; Jaaziel E. García-Hernandez; Daniel A. Toledo-Rodríguez; Nikolaos V. Schizas; Lisa J. Rodrigues (Marine Pollution Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Impact of melatonin on inflammatory cytokine profiles in 24-hour cultured equine uterine explants’ - Murilo F. Rodrigues; Adriana P. Neves; Rogério Ferreira; Gilson A. Pessoa; Denise N. Araujo; Guilherme V. de Souza (Journal of Equine Veterinary Science, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Effects of red light-emitting diode therapy in imiquimod-induced psoriasis in mice - Mab P. Corrêa; Rebeca D. Correia-Silva; Diego D. Santos; Nathália Rodrigues-Silva; Pâmela P. Borges; Silvana Sandri; Karin V. Greco; Cristiane D. Gil (Journal of Photochemistry and Photobiology B: Biology, 2026)

Tackling CECs and antimicrobial resistant bacteria in hospital wastewater using biological and AOP hybrid technologies - Eloísa Stéphanie da Silva; Alessandra S. Martins; Lara Fabian S. Ribeiro; Jhonatha Rodrigo Cordeiro-Moura; Daniel A.S. Rodrigues; Renata Cristina Picão; Maria Clara V. M. Starling; Camila C. Amorim (Bioresource Technology, 2026)

Isotopic niche analysis of sympatric hermit crabs (Decapoda: Anomura) reveals different trends among generalist consumers - G. F. B. Rodrigues; V. E. Costa; A. L. Castilho (Hydrobiologia, 2026)

Hemocyte Apoptosis as a Biomarker of Environmental Stress in Aeglid Species (Decapoda: Anomura) - Renan A. P. dos Santos; Graziela G. Romagnoli; George S. Yasui; Isabela R. R. Moraes; Mariana V. Capparelli; Gabriel F. B. Rodrigues; Larissa R. C. de Oliveira; Antonio L. Castilho (Bulletin of Environmental Contamination and Toxicology, 2026)

Cryopreservation of fish ovarian tissue post-mortem: Solution for emergency genetic preservation - Thaiza R. de Freitas; Lis S. Marques; Raquel S. dos Santos; Renata V. Dantas; Thales S. França; Rômulo B. Rodrigues; Karel G. Torres Lozano; Eduardo Albuquerque; Diógenes H. Siqueira-Silva; Tiantian Zhang; Danilo P. Streit (Cryobiology, 2025)

Soil carbon dynamics, nutrient enhancement, and maize productivity under traditional cattle corralling practices in northern Benin - Awouminassi M. Atakoun; Pierre G. Tovihoudji; Rodrigue V. C. Diogo; William Amponsah; Murilo dos Santos Vianna; Thomas Gaiser; Nicholas Kyei-Baffour; Boateng Kyereh (Nutrient Cycling in Agroecosystems, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Green infrastructure for urban climate mitigation and adaptation: methods, strategies, and typology selection based on ecosystem services - B. N. Rodrigues; A. L. F. Favoreti; V. E. Molina Júnior; C. M. Silva; F. B. Canteras (International Journal of Environmental Science and Technology, 2025)

Coastal fallout of settleable particulate matter: Metal bioaccumulation and sublethal toxicity in estuarine bivalves with implications for human health - Luís Felipe de Almeida Duarte; Andressa dos Santos Barbosa Ortega; Marina de Souza Paço; Caio Rodrigues Nobre; Helen Sadauskas-Henrique; Paloma Kachel Gusso-Choueri; Iara Costa Souza; Mariana V. Carvalho; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Marisa Narciso Fernandes; Camilo Dias Seabra Pereira (Marine Pollution Bulletin, 2025)

The use of electrodialysis for the removal of metals from aqueous solutions - C. L. S. dos Santos; M. S. Rodrigues; F. S. Moreira; V. L. Cardoso; M. M. de Resende (International Journal of Environmental Science and Technology, 2025)

Understanding the effects of hematite and brucite additions on fresh- and hardened-state properties of metakaolin-based geopolymer cements - Jie Ren; Mohammad G. Matar; Naiara Rodrigues Tonin; Christine Pu; Claire E. White; Wil V. Srubar (Applied Clay Science, 2025)

Tides of rebirth: A stratigraphic perspective on the Lazarus effect in freshwater bivalves in the Aptian-Albian Romualdo Formation, Araripe Basin, Brazil - Marcello G. Simões; Vitor B. Guerrini; Victor R. Silva; Filipe G. Varejão; Suzana A. Matos; Mariza G. Rodrigues; Lucas V. Warren; Mario L. Assine; Franz T. Fürsich (Cretaceous Research, 2025)

Recent Advances in Subcritical Water Pretreatment of Lignocellulosic Biomass: Integrating Modern Extraction Techniques for Biorefinery Applications - Carolina E. Demaman Oro; Jéssica Mulinari; Carlos Rafael Silva de Oliveira; Afonso Henrique da Silva Júnior; Éllen Francine Rodrigues; Rogério Marcos Dallago; Marcus V. Tres (BioEnergy Research, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Synthesis of autoinducer-2 prodrugs and analogues as a new antimicrobial strategy - Peter Kis; Miguel V. Rodrigues; Karina B. Xavier; M. Rita Ventura (Phytochemistry Letters, 2025)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Combination therapies and novel delivery systems: a new frontier in overcoming TRAIL resistance in gastric cancer - Paul Rodrigues; Abdulrahman T. Ahmed; Majid Jabir; Khetam Habeeb Rasool; Soumya V. Menon; Aryantika Sharma; M. Ravi Kumar; Matheel D. Al-Sabti; Sabrean F. Jawad; Salah Hassan Zain Al-Abdeen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Coevolution of life and environment during the Ediacaran-Cambrian transition: Clues from litho-, bio-, and chemostratigraphy of the Corumbá Group, Brazil - Henrique Albuquerque Fernandes; Gustavo Paula Santos; Luiz Gustavo Pereira; Leonardo Thomaz Rimi; Thales Pescarini; Eric Elias; Carolina Bedoya Rueda; Vinícius Cardoso Lucas; Larissa Rodrigues; Karina Mazzamuto; Ligia Stama; Sergio Caetano Filho; et al. (Precambrian Research, 2025)

Co-fermentation of sugar-alcohol industry waste to produce hydrogen and value-added metabolites - Bruna S. Dionizio; Camila A.B.S. Rabelo; Caroline V. Rodrigues; Franciele P. Camargo; Edson L. Silva; Dulce H.F. de Souza; Maria Bernadete A. Varesche (Bioresource Technology Reports, 2025)

CFD modelling of an urban microclimate during a heat wave: Coupling solar radiation and heat transfer - D. Nascimento; A. Ascenso; D. Lopes; M. Lopes; V. Rodrigues (Urban Climate, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

ESTIMET: Enhanced and Spatial-Temporal Improvement of MODIS EvapoTranspiration algorithm for all sky conditions in tropical biomes - Cinthia M.A. Claudino; Guillaume F. Bertrand; Rodolfo L.B. Nóbrega; Cristiano das N. Almeida; Ana Cláudia V. Gusmão; Suzana M.G.L. Montenegro; Bernardo B. Silva; Eduardo G. Patriota; Filipe C. Lemos; Jaqueline V. Coutinho; José Welton Gonçalo de Sousa; João M. Andrade; et al. (Remote Sensing of Environment, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Saguinus martinsi: predicted loss of habitat suitability following global warming and insights for the conservation of the species - Angele Tatiane Martins-Oliveira; Pedro V. Eisenlohr; Gustavo Rodrigues Canale; João Carlos Pires-Oliveira; Leandro José-Silva; Lucas Barros-Rosa; Leandro Santana Moreira; Fabiano Rodrigues de Melo (Primates, 2025)

Relationship between estrus and reactivity on the reproductive performance of beef cows - Francisco A.R. Catalano; Luiz E. Kozicki; Isis V. Rodrigues; Ruan R. Daros (Applied Animal Behaviour Science, 2025)

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Unique conifer assemblage from Late Jurassic-Early Cretaceous deposits (NE Brazil) unveils the paleoclimate and paleobiogeography in the interior of equatorial Gondwana - Domingas Maria da Conceição; Mário G.F. Esperança Júnior; William V. Gobo; Roberto Iannuzzi; Maria E.P. Batista; Daniel Rodrigues do Nascimento; Wellington Ferreira da Silva Filho; Rodrigo Scalise Horodysk; Marion K. Bamford; Lutz Kunzmann (Cretaceous Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Exploring plant functional traits and their relationship to biomass dynamics in secondary forests in Eastern Amazonia - Luane Botelho; Fernando Elias; Beatriz V. Barbosa; Karoline C. Silva; Vanessa Negrão-Rodrigues; Euciney E.S. Barbosa; Jucelino S. Coutinho; Joice Ferreira; Jos Barlow; Grazielle Sales Teodoro (Flora, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Cross‐Taxa Analysis of Long‐Term Data Reveals a Positive Biodiversity‐Stability Relationship With Taxon‐Specific Mechanistic Underpinning - Arthur V. Rodrigues; Tuuli Rissanen; Mirkka M. Jones; Ida‐Maria Huikkonen; Otso Huitu; Erkki Korpimäki; Mikko Kuussaari; Aleksi Lehikoinen; Andreas Lindén; Hannu Pietiäinen; Juha Pöyry; Pasi Sihvonen; et al. (Ecology Letters, 2025)
Anthropogenic environmental change is altering biodiversity at unprecedented rates, threatening the stability of ecosystem services on which humans depend. However, most of what is known about biodiversity–stability relationships comes from experimental studies making extrapolation to real ecosystems difficult. Here, we ask whether the shape and underlying mechanisms of the biodiversity–stability relationship vary among taxa in real‐world communities. Our study harnesses the power of six terrestrial and aquatic long‐term monitoring datasets, encompassing entire assemblages at hundreds of georeferenced sites providing 20 years long community measurements, covering a 1200 km latitudinal gradient across Finland. In general, we detect a positive relationship between species richness and stability. Structural equation modelling reveals that this relationship is modified by functional trait community composition, with specific mechanisms varying among the taxa. Our study is among the first to highlight the importance of functional traits in elucidating both general and taxon‐specific impacts of biodiversity on community stability.

Key patterns in exceptional fossil preservation since the rise of metazoans - Filipe G. Varejão; Rodrigo I. Cerri; Lucas V. Warren; Mariza G. Rodrigues; Stephen J. Puetz; Paloma P. de Lorenso; Marcello G. Simões (Earth-Science Reviews, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Assessing the predicted impact of single amino acid substitutions in calmodulin for CAGI6 challenges - Paola Turina; Giuditta Dal Cortivo; Carlos A. Enriquez Sandoval; Emil Alexov; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Piero Fariselli; Lukas Folkman; Akash Kamandula; Panagiotis Katsonis; et al. (Human Genetics, 2025)

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Contextualizing the Upper Paleolithic of the Armenian Highlands: New data from Solak-1, central Armenia - Tanner Z. Kovach; Artur Petrosyan; Keith N. Wilkinson; Yannick Raczynski-Henk; Kathleen Rodrigues; Ellery Frahm; Emily Beverly; Jayson P. Gill; Jennifer E. Sherriff; Boris Gasparyan; Hayk G. Avetisyan; Artak V. Gnuni; et al. (Journal of Human Evolution, 2025)

Impact of urban disturbance on soil insect communities in a Brazilian Atlantic Forest biological station - Felipe Ferraz Figueiredo Moreira; Juliana Mourão dos Santos Rodrigues; Marcos Krull; Raquel G. Boullosa; Rosana Gentile; Karina Cunha Sant’ana; Marianna V. P. Simões (Urban Ecosystems, 2025)
Urbanization constitutes a major threat to biodiversity. Understanding its effects on insect communities is relevant because they are key elements of trophic interactions, and indicators and targets of conservation. Herein, we investigated the influence of meteorological and habitat factors on the soil entomofauna in three areas with distinct levels of urbanization at the Parque Estadual da Pedra Branca, Brazil. We investigated whether community structure differs among areas with different levels of urbanization, and how changes in the environment affect soil insect community composition and distribution. We systematically monitored communities for 12 months in three areas along a gradient of anthropogenic disturbance, representing preserved secondary forest, disturbed forest and peridomicile areas. The results revealed that the degree of urbanization affects insect communities, with a strong effect of habitat factors, such as canopy cover, presence of flooded areas, quantity of fallen trunks and mean temperature. Insect abundance did not show significant differences among areas, while biomass was higher in disturbed forest than in preserved forest and peridomicile areas. Additionally, insect richness and diversity were higher in preserved and disturbed forests than in peridomicile areas, with no significant difference between preserved and disturbed forests. Our results can be used to enhance the understanding of the effects of urbanization on taxonomically and functionally diverse groups of insects, and to advise residents and urban planners about the consequences of urbanization on biodiversity and ecosystem services in urban-sylvatic interface areas.

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Schwann cells exposed to articaine display distinct toxic pathways compared to lidocaine - Gustavo H. Rodrigues da Silva; Luís F. Mendes; Gabriela Geronimo; Ludmilla D. de Moura; Juliana S. Ruas; Roger F. Castilho; Helon G. Cordeiro; Carmen V. Ferreira; Eneida de Paula; Iola F. Duarte (Chemico-Biological Interactions, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Florida mangrove dieback on a decadal and centennial timescales - Marcelo C.L. Cohen; Diana Paola Cardenas Ruiz; Erika Rodrigues; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Luiz C.R. Pessenda; Alejandro Antonio Aragón-Moreno; Junghyung Ryu; Sérgio Nunes (Science of The Total Environment, 2024)

Conversion of tomato waste into a poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) by a mixed microbial community - Thomas Rodrigues; Cristiana V. Torres; Patrícia Freitas; Luísa A. Neves; Mónica Carvalheira; Maria A.M. Reis; Filomena Freitas (Journal of Environmental Chemical Engineering, 2024)

Comparing net zero pathways across the Atlantic A model inter-comparison exercise between the Energy Modeling Forum 37 and the European Climate and Energy Modeling Forum - Luis Sarmiento; Johannes Emmerling; Robert Pietzcker; Vassilis Daioglou; Francesco Dalla Longa; Mark M. Dekker; Laurent Drouet; Amir Fattahi; Panagiotis Fragkos; Hauke T. J. Henke; Oliver Fricko; Leonard Göke; et al. (Energy and Climate Change, 2024)

Has unsustainable groundwater use induced low flow regimes in the Urucuia Aquifer System? An urgent call for integrated water management - André F. Rodrigues; Bruno M. Brentan; Marta V. Ottoni; Jhones S. Amorim; Maria A.A. Mourão; Nilton Curi; Junior C. Avanzi; Carlos R. de Mello (Journal of Environmental Management, 2024)

Cardioprotection of Canagliflozin, Dapagliflozin, and Empagliflozin: Lessons from preclinical studies - Rayla Rodrigues Soares; Larissa Freitas Viggiani; Juliano Moreira Reis Filho; Julliane V. Joviano-Santos (Chemico-Biological Interactions, 2024)

Deepening our understanding of the environmental influences on the reproductive dynamics of the main fishery stock of Argentine hake, Merluccius hubbsi , in the southwestern Atlantic Ocean - Mariano Elisio; Marina V. Diaz; Ezequiel Leonarduzzi; Karina A. Rodrigues; Juan M. Burla; Gustavo J. Macchi (Fisheries Oceanography, 2024)
This study analyzed the inter‐annual variability in the reproductive dynamics of the Argentine hake from Patagonian waters during the last 20 years concerning the environmental conditions and the nutritional status of females. Macroscopic and histological information on gonadal maturity, female condition factor (K), and oceanographic data at different sampling sites throughout the studied region were obtained from research surveys carried out during the main spawning season of this species. Four stages, according to the maturity ovarian phases composition, were assigned annually at each sampling site to assess reproductive dynamics: vitellogenesis, ovulation, regression, and resting. The spatial pattern of inter‐annual variability in reproductive dynamics was described, and the influence of temperature and female condition on the probability of ovulation and regression was assessed using generalized linear models. The area with the lowest inter‐annual variability in the hake reproductive dynamics was observed between 43 and 45°S (50 to 80 m depth) in relation to ovulation events. The vitellogenesis stage was more frequently found adjacent to the reproductive area, whereas the regression was mainly observed in deeper waters. Both bottom and surface temperatures explained the ovulation and regression stages, showing a positive and negative relationship, respectively. Lower values of the K factor, associated with low food availability, were further linked to the occurrence of regression. Finally, it is worth noting that the relationship observed between the ovulation/spawning dynamics of Argentine hake and water temperature suggests that the reproductive success of this species could be affected in the future scenario of climate change.

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Holistic evaluation of the environmental impacts of shipping in the sensitive region of Ria de Aveiro - A. Monteiro; V. Rodrigues; A. Picado; J.M. Dias; N. Abrantes; A. Ré; M. Rosa; M. Russo; A. Barreirinha; M. Potiris; M. Aghito; R. Hänninen; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Setting up a CFD model to evaluate the impact of green infrastructures on local air quality - V. Rodrigues; B. Augusto; K. Oliveira; A. Ascenso; S. Rafael; D. Nascimento; A. I. Miranda (Air Quality, Atmosphere & Health, 2024)
Green infrastructures have been pointed out as innovative solutions to deal with current and future challenges related to air pollution and climate change. Although the potential of green infrastructures, such as green walls and green roofs, to mitigate air pollution has been documented, evidence at a local scale is still limited. This work aims to increase knowledge about the potentialities of green infrastructures in improving local air quality, focusing on particulate matter, nitrogen dioxide and ozone pollutants, and by using a local-scale computational fluid dynamics model. The ENVI-met model was applied to a particular hour of a summer day over a built-up environment centred on a main avenue in the city of Lisbon (Portugal). The dimensions of the computational domain are 618 m × 594 m × 143 m, and it contains 184 buildings, with the tallest building being 56 m. In addition to the baseline simulation, modelling was also done considering the application of green walls and green roofs to specific buildings located near the main avenue, together with a green corridor. The overall results show no disturbances exerted by green walls on the turbulent flow dynamics and on the air quality levels when compared to the baseline scenario (without green walls). The integrated scenario, which includes green walls, green roofs and a green corridor, will lead to potential local benefits of green infrastructures on O 3 concentrations, followed by variable impacts on NO 2 and particulate matter concentrations.

P02-28 Microfluidics technology as a tool to improve maturation and drug metabolism capacity of stem cell-derived hepatocytes in vitro - J.S. Rodrigues; S. Relvas; P.G. Condelipes; B. Silva; R. Bozzo; P. Guedes de Pinho; V. Chu; F. Remião; J.P. Conde; J.P. Miranda (Toxicology Letters, 2024)

P01-23 Optimization of predictive liver toxicity modeling based on the drug-induced cholestasis index - A. Drees; V. Nassiri; A. Tabernilla Garcia; J. Serroyen; E. Gustin; B. dos Santos Rodrigues; D.M. Moss; A. De Smedt; M. Vinken; F. Van Goethem; J. Sanz-Serrano (Toxicology Letters, 2024)

Bioactivity of Piper aduncum and Piper marginatum essential oils on Planococcus citri (RISSO, 1813) (Hemiptera: Pseudococcidae) - Carla H. M. De Lima; Claudio A. G. Camara; Vaneska B. Monteiro; Mayara F. Santos; Wendel J. T. Pontes; Marcílio M. Moraes; Lucas V. B. Rodrigues (International Journal of Tropical Insect Science, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Chronic Cadmium Exposure can Alter Energy Allocation to Physiological Functions in the Shrimp Penaeus vannamei - Juliana Rodrigues da Costa; Mariana V. Capparelli; Pedro Magalhães Padilha; Emanuelle Borges; Andressa C. Ramaglia; Michelle Roberta dos Santos; Alessandra Augusto (Archives of Environmental Contamination and Toxicology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - L. A. Rodrigues; A. A. Almeida; A. P. Agrizii; N. Pacheco; B. C. R. Carvalho; A. C. Zanatta; M. Kohlhoff; C. M. M. E. Torres; G. C. Bressan; J. P. V. Leite (Natural Product Research, 2024)

Impact of washing and freezing on nutritional composition, bioactive compounds, antioxidant activity and microstructure of mango peels - Sara Marçal; Sérgio Sousa; Helena Araújo-Rodrigues; Inês V. Silva; Débora A. Campos; Manuela Pintado (Food Chemistry, 2024)

Blown film of PLA for packaging with green tea and fish industrial residues: An insight on their properties - Pedro V. Rodrigues; Ana B. Cunha; Mariana A. Andrade; Fernanda Vilarinho; Ana Vera Machado; M. Cidália R. Castro (Food Packaging and Shelf Life, 2024)

Anatomical, histochemical, and developmental approaches reveal the long-term functioning of the floral nectary in Tocoyena formosa (Rubiaceae) - Juliana V. Izquierdo; Yve Canaveze; Silvia Rodrigues Machado; Felipe W. Amorim (The Science of Nature, 2024)

Do hurricanes or freezing events regulate the sustainability of subtropical mangroves on the Gulf of Mexico coast? - Marcelo C. L. Cohen; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Sergio Nunes; Erika Rodrigues; Luiz C. R. Pessenda; Nicholas Culligan (Regional Environmental Change, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Assessment of the impact of conservation measures by modeling soil loss in Minas Gerais, Brazil - A. K. M. Soares; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2024)

Herodotools: An R package to integrate macroevolution, biogeography and community ecology - Gabriel Nakamura; Arthur V. Rodrigues; André Luís Luza; Renan Maestri; Vanderlei Debastiani; Leandro Duarte (Journal of Biogeography, 2024)
Aim Speciation, extinction and historical dispersal are the ultimate factors generating and maintaining biodiversity. However, methods of macroevolution used to detect historical processes usually ignore the variation of macroevolutionary processes at scales finer than entire regions. Likewise, biogeography and community ecology often ignore deep‐time evolutionary processes. To overcome this problem, it is necessary to integrate data from ancestral state reconstructions, current species distributions and biogeographical regionalization. Herodotools is an R package designed to perform this integration. Location Global application, with an example from Neotropics. Major taxa studied Any taxa, with an example from small rodents (genus Akodon and subfamily Sigmodontinae). Methods Herodotools streamline analyses of historical biogeography, including regionalization, calculation of assemblage age, lineage in situ diversification and community phylogenetic metrics, merging species occurrence with macroevolutionary methods of ancestral area and trait reconstruction. The main functions of our R package are presented with toy examples and by analysing the historical biogeography of small rodent assemblages in the Neotropics. Results Our package can integrate methods from biogeography, macroevolution and community ecology, allowing us to downscale the effects of historical processes and calculate important historical variables (e.g., age of assemblages, in situ diversification, phylogenetic regionalization, phylogenetic transition zones, metrics of trait macroevolutionary dynamics and new metrics of phylogenetic diversity and endemism) in different scales, from entire regions to communities of co‐occurrent species. Main Conclusions Herodotools is the first platform to streamline the analysis of historical biogeography, enabling a better understanding of historical processes at different levels of organization, from local assemblages to entire biogeographical regions and incorporating macroevolutionary models in commonly used community phylogenetic metrics. This integration bridges the gap between macroevolutionary, biogeography and community ecology methods.

Anti-inflammatory and antiproliferative activity of Helichrysum odoratissimum Sweet. against lung cancer - Tenille Esmear; Danielle Twilley; Velaphi Clement Thipe; Kattesh V. Katti; Vusani Mandiwana; Michel Lonji Kalombo; Suprakas Sinha Ray; Rirhandzu Rikhotso-Mbungela; Venugopal Reddy Bovilla; SubbaRao Madhunapantula; Lenka Langhanshova; Catarina Roma-Rodrigues; et al. (South African Journal of Botany, 2024)

Negative effects of ghost nets on Mediterranean biodiversity - Júlia Fernandes Perroca; Tommaso Giarrizzo; Ernesto Azzurro; Jorge Luiz Rodrigues-Filho; Carolina V. Silva; Marlene S. Arcifa; Valter M. Azevedo-Santos (Aquatic Ecology, 2024)

Fluoxetine alters rat's milk properties causing impact on offspring's development - Gabriel R. Abreu; Julia Zaccarelli-Magalhães; Laís S. Féba; Emily Y. Penna; Julia P. Silva; Mariana V. Teixeira; Marianna Manes; Guilherme A. Vergara; Leonardo M.A. Rodrigues; André R. Fukushima; Esther L. Ricci; Helenice S. Spinosa (Toxicology and Applied Pharmacology, 2024)

Rainfall and rain pulse role on energy, water vapor and CO2 exchanges in a tropical semiarid environment - Cláudio M. Santos e Silva; Bergson G. Bezerra; Keila R. Mendes; Pedro R. Mutti; Daniele Tôrres Rodrigues; Gabriel Brito Costa; Pablo Eli Soares de Oliveira; Jean Reis; Thiago V. Marques; Rosaria Rodrigues Ferreira; Suany Campos; Tarsila M. Ramos; et al. (Agricultural and Forest Meteorology, 2024)

Effects of chemical aging on carbonaceous materials: Stability of water-dispersible colloids and their influence on the aggregation of natural-soil colloid - Laís G. Fregolente; Maria T. Rodrigues; Naiara C. Oliveira; Bruno Sousa Araújo; Ícaro V. Nascimento; Antonio G. Souza Filho; Amauri J. Paula; Mirian C.G. Costa; Jaedson C.A. Mota; Odair P. Ferreira (Science of The Total Environment, 2023)

Uncovering the phenolic diversity of Guabiju fruit: LC-MS/MS-based targeted metabolomics approach - Liziane V. Spinelli; Michel J. Anzanello; Rodrigo Areze da Silva Santos; Caroline Carboni Martins; Justine Freo Saggin; Magnólia Aparecida Silva Da Silva; Eliseu Rodrigues (Food Research International, 2023)

A cyclic sorption-reaction process for continuous synthetic methane production from flue gas and green hydrogen - Joana A. Martins; Vanessa F.D. Martins; Carlos V. Miguel; Alírio E. Rodrigues; Luis M. Madeira (Chemical Engineering Journal, 2023)

Metallothionein expression in the central nervous system in response to chronic heavy metal exposure: possible neuroprotective mechanism - A. Navarro-Sempere; P. Martínez-Peinado; A. S. Rodrigues; P. V. Garcia; R. Camarinho; G. Grindlay; L. Gras; M. García; Y. Segovia (Environmental Geochemistry and Health, 2023)
It has been reported that volcanoes release several tonnes of mercury per year among other heavy metals through eruptions, fumaroles, or diffuse soil degassing. Since a high percentage of the world's population lives in the vicinity of an active volcano, the aim of this study is to evaluate the accumulation of these metals in the central nervous system and the presence of cellular mechanisms of heavy metal detoxification such as metallothioneins. To carry out this study, wild mice (Mus musculus) chronically exposed to an active volcanic environment were captured in Furnas village (Azores, Portugal) and compared with those trapped in a reference area (Rabo de Peixe, Azores, Portugal). On the one hand, the heavy metal load has been evaluated by analyzing brain and cerebellum using ICP-MS and a mercury analyzer and on the other hand, the presence of metallothionein 2A has been studied by immunofluorescence assays. Our results show a higher load of metals such as mercury, cadmium and lead in the central nervous system of exposed mice compared to non-exposed individuals and, in addition, a higher immunoreactivity for metallothionein 2A in different areas of the cerebrum and cerebellum indicating a possible neuroprotection process.

Composition and diversity of fish assemblages along a shallow beach of a neotropical coastal lagoon - Catarina de C.A. Frischknecht; David V. Dantas; Jorge L. Rodrigues-Filho; Eduardo Gentil (Regional Studies in Marine Science, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Nickel enhances rice resistance against Bipolaris oryzae infection - Caroline Hawerroth; Andersom M. Einhardt; Bianca A. Fontes; Verônica V. Brás; Samuel V. Valadares; Fabrício A. Rodrigues (Plant and Soil, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Spatial distribution of the greater rhea, Rhea americana (Linnaeus, 1758), in Rio Grande do Sul, southern Brazil: citizen-science data, probabilistic mapping, and comparison with expert knowledge - André L. Luza; Arthur V. Rodrigues; Louisa Mamalis; Viviane Zulian (Ornithology Research, 2023)

Transforming iron ore processing – Simplifying the comminution and replacing reverse flotation with magnetic and gravity separation - Armando F. d. V. Rodrigues; Homero Delboni; Klaydison Silva; James Zhou; Kevin P. Galvin; Lev O. Filippov (Minerals Engineering, 2023)

The paleoenvironmental and thermal histories of the Permian Irati Formation shale in the Paraná Basin, Brazil: An integrated approach based on mineralogical and organic imprints - Haline V. Rocha; Lucy G. Sant’Anna; Cristina F.A. Rodrigues; Márcia Mendes; Zélia Pereira; Gilda Lopes; Paulo Fernandes; Egberto Pereira; Colombo C.G. Tassinari; Manuel J. Lemos de Sousa (Marine and Petroleum Geology, 2023)

Removal of Reactive Dyes from a Real Bichromatic Textile Effluent Employing Bio-Based Nanomagnetic Adsorbents - Kátia C. H. Bezerra; Jacqueline R. Nascimento; Tiago D. Martins; Sherlan G. Lemos; Elma N. V. M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Water, Air, & Soil Pollution, 2023)

An exonuclease V homologue is expressed predominantly during early megasporogenesis in apomictic Brachiaria brizantha - Diva M. A. Dusi; Elizângela R. Alves; Gláucia B. Cabral; Luciane V. Mello; Daniel J. Rigden; Érica D. Silveira; Márcio Alves-Ferreira; Larissa A. Guimarães; Ana Cristina M. M. Gomes; Júlio C. M. Rodrigues; Vera T. C. Carneiro (Planta, 2023)

Sex and the Estrous-Cycle Phase Influence the Expression of G Protein-Coupled Estrogen Receptor 1 (GPER) in Schizophrenia: Translational Evidence for a New Target - Francisco Eliclécio Rodrigues da Silva; Rafaela Carneiro Cordeiro; Camila N. de Carvalho Lima; Pablo Leal Cardozo; Germana Silva Vasconcelos; Aline Santos Monte; Lia Lira Olivier Sanders; Silvânia Maria Mendes Vasconcelos; David Freitas de Lucena; Breno Fiuza Cruz; Rodrigo Nicolato; Mary V. Seeman; et al. (Molecular Neurobiology, 2023)

Application of essential oils as sanitizer alternatives on the postharvest washing of fresh produce - Jessica S. Pizzo; Jesui V. Visentainer; Andre L.B.R. da Silva; Camila Rodrigues (Food Chemistry, 2023)

Spray Freeze Drying of Biologics: A Review and Applications for Inhalation Delivery - Susana Farinha; João V. Sá; Paulo Roque Lino; Marco Galésio; João Pires; Miguel Ângelo Rodrigues; João Henriques (Pharmaceutical Research, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Correction to: The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

The meaning of the word elegance as a wine descriptor: Effect of expertise and wine type - Hester Shepherd; Wendy V. Parr; Grégory Lo Monaco; Heber Rodrigues (Food Research International, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Withalutin, a new cytotoxic withanolide from Athenaea velutina (Sendtn.) D’Arcy - Alisson A. Almeida; Betania B. Cota; Laís A. Rodrigues; Luana L. Dutra; Markus Kohlhoff; Gustavo C. Bressan; Geraldo C. Brandão; João P. V. Leite (Natural Product Research, 2022)

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2022)

Response of benthic dinoflagellates Amphidinium carterae and Bysmatrum gregarium to salinity changes and prolonged darkness: elucidation through laboratory experiments - R. V. Rodrigues; J. S. Patil (Aquatic Ecology, 2022)

Cerrado deforestation threatens regional climate and water availability for agriculture and ecosystems - Ariane A. Rodrigues; Marcia N. Macedo; Divino V. Silvério; Leandro Maracahipes; Michael T. Coe; Paulo M. Brando; Julia Z. Shimbo; Raoni Rajão; Britaldo Soares‐Filho; Mercedes M. C. Bustamante (Global Change Biology, 2022)
The Brazilian Cerrado is one of the most biodiverse savannas in the world, yet 46% of its original cover has been cleared to make way for crops and pastures. These extensive land‐use transitions (LUTs) are expected to influence regional climate by reducing evapotranspiration (ET), increasing land surface temperature (LST), and ultimately reducing precipitation. Here, we quantify the impacts of LUTs on ET and LST in the Cerrado by combining MODIS satellite data with annual land use and land cover maps from 2006 to 2019. We performed regression analyses to quantify the effects of six common LUTs on ET and LST across the entire gradient of Cerrado landscapes. Results indicate that clearing forests for cropland or pasture increased average LST by ~3.5°C and reduced mean annual ET by 44% and 39%, respectively. Transitions from woody savannas to cropland or pasture increased average LST by 1.9°C and reduced mean annual ET by 27% and 21%, respectively. Converting native grasslands to cropland or pasture increased average LST by 0.9 and 0.6°C, respectively. Conversely, grassland‐to‐pasture transitions increased mean annual ET by 15%. To date, land changes have caused a 10% reduction in water recycled to the atmosphere annually and a 0.9°C increase in average LST across the biome, compared to the historic baseline under native vegetation. Global climate changes from increased atmospheric greenhouse gas concentrations will only exacerbate these effects. Considering potential future scenarios, we found that abandoning deforestation control policies or allowing legal deforestation to continue (at least 28.4 Mha) would further reduce yearly ET (by −9% and −3%, respectively) and increase average LST (by +0.7 and +0.3°C, respectively) by 2050. In contrast, policies encouraging zero deforestation and restoration of the 5.2 Mha of illegally deforested areas would partially offset the warming and drying impacts of land‐use change.

Land cover transitions and effects of transhumance on available forage biomass of rangelands in Benin - James Ellison; Katja Brinkmann; Rodrigue V. Cao Diogo; Andreas Buerkert (Environment, Development and Sustainability, 2022)
This study examined the effects of transhumance pressure on total abavoe-ground biomass and forage availability on rangelands in Benin. We also investigated the implications of land cover transitions on rangelands over a 31-year period. Our work was carried out in three regions of Benin representing distinct phytogeographic regimes: Ketou, Tchaourou, and Sinende. Ground-truthing and biomass sampling of the herbaceous and phanaerophyte strata were carried out between the 2016 peak vegetation period and the onset of the 2017 rainy season. Herbaceous biomass was determined by destructive sampling, and biomass of shrub and trees was estimated using non-destructive sampling and allometric equations. Historical and present-day Landsat data allowed an analysis of land cover change for the 1986–2002 and 2002–2017 periods. Land cover analyses yielded evidence of significant expansion of agricultural areas, especially in the latter period. The data also revealed progressive landscape fragmentation and transformations to a land cover of reduced total phytomass. There were no long-term effects of transhumance on trees, but likely on herbaceous biomass. Land cover changes in the study regions seem primarily the result of population pressure, infrastructural changes, persisting norms, and traditions regarding environmental management and the increasing popularity of livestock keeping as an insurance strategy. Rangeland transformations had negative impacts on transhumant herds’ mobility and forage availability. As rangeland stability and consent between agricultural and pastoral land users are at a tipping point, informed policies, and land use planning that foster compromises among all stakeholders are needed.

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

Diversity of Bryozoa in Iceland - Joana Micael; Nina V. Denisenko; Sindri Gíslason; Guðmundur Guðmundsson; Piotr Kukliński; Pedro Rodrigues (Polar Biology, 2022)

Epithelial morphometric alterations and mucosecretory responses in the nasal cavity of mice chronically exposed to hydrothermal emissions - R. Camarinho; A. Madrero Pardo; P. V. Garcia; A. S. Rodrigues (Environmental Geochemistry and Health, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Comparison of sugarcane pressmud with traditional low-cost materials for adsorption of lead and zinc in mining areas - I. M. Raimondi; E. M. Vieira; L. A. A. Vaz; V. G. S. Rodrigues (International Journal of Environmental Science and Technology, 2022)

QSAR-Guided Proposition of N-(4-methanesulfonyl)Benzoyl-N’-(Pyrimidin-2-yl)Thioureas as Effective and Safer Herbicides - Natânia E. Rodrigues; Adriana C. de Faria; Ingrid V. Pereira; Elaine F. F. da Cunha; Matheus P. Freitas (Bulletin of Environmental Contamination and Toxicology, 2022)

Occurrence of Volcanogenic Inorganic Mercury in Wild Mice Spinal Cord: Potential Health Implications - A. Navarro-Sempere; M. García; A. S. Rodrigues; P. V. Garcia; R. Camarinho; Y. Segovia (Biological Trace Element Research, 2022)
Mercury accumulation has been proposed as a toxic factor that causes neurodegenerative diseases. However, the hazardous health effects of gaseous elemental mercury exposure on the spinal cord in volcanic areas have not been reported previously in the literature. To evaluate the presence of volcanogenic inorganic mercury in the spinal cord, a study was carried out in São Miguel island (Azores, Portugal) by comparing the spinal cord of mice exposed chronically to an active volcanic environment (Furnas village) with individuals not exposed (Rabo de Peixe village), through the autometallographic silver enhancement histochemical method. Moreover, a morphometric and quantification analysis of the axons was carried out. Results exhibited mercury deposits at the lumbar level of the spinal cord in the specimens captured at the site with volcanic activity (Furnas village). A decrease in axon calibre and axonal atrophy was also observed in these specimens. Given that these are relevant hallmarks in the neurodegenerative pathologies, our results highlight the importance of the surveillance of the health of populations chronically exposed to active volcanic environments.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Correction to: Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Attraction of whitefly Aleurodicus cocois mediated by cashew volatiles - Wenner V. A. Saraiva; Nívia S. Dias-Pini; Elenilson G. Alves Filho; José W. S. Melo; Marilene Fancelli; Cristiane R. Coutinho; Guilherme J. Zocolo; Tigressa H. S. Rodrigues; Poliana M. Duarte; Vitor H. M. Macedo; Elaine S. S. Goiana (Phytoparasitica, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Onset and demise dates of the rainy season in the South American monsoon region: A cluster analysis result - Maria A. M. Rodrigues; Sâmia R. Garcia; Mary T. Kayano; Alan J. P. Calheiros; Rita V. Andreoli (International Journal of Climatology, 2022)
This work proposes an adaptation of the method developed in previous papers to determine the onset and demise of the rainy season (ONR and DER) dates in the areas of the South American monsoon system (SAMS) based on the pentad antisymmetric outgoing long‐wave radiation (AOLR). In those papers, the sign change of the mean AOLR in the central Amazon Basin (CAM) and western central Brazil (WCB) from positive to negative defined the ONR, from negative to positive, the DER dates. Since the monsoon convection presents a northwest–southeast oriented progression, the antisymmetric area to the WCB was selected subjectively. Thus, here we propose to use the Ward hierarchical clustering method to select areas in the SAMS and in the northern tropical America (NTA) for the regionalized AOLR calculation. The significant (at the 95% confidence level) negative correlations with the largest magnitude among the clusters in the SAMS and NTA and the outgoing long‐wave radiation (OLR) and precipitation annual cycles in each group define the pairs to calculate the AOLR. Then, the AOLR time series is calculated and subjected to a 5‐pentad running mean filter. This method keeps the climatological features of the convection annual cycle such that the closer (farther) the pair is to the equator the longer (shorter) the rainy season. The ONR and DER dates found with this new method are remarkably close to those found previously. Therefore, the new method proposed here highlights regional aspects of rainy season and can easily be automatized for its routine application at the operational climate monitoring centres, for instance at INPE. This is the most important advantage of the method and might be relevant to the SAMS rainy season monitoring.

Preformulation and characterization of raloxifene-loaded lipid nanoparticles for transdermal administration - Guilherme L. Alves; Fernanda V. Teixeira; Priscila Bianca Rodrigues da Rocha; Anna Paula Krawczyk-Santos; Lígia Marquez Andrade; Marcilio Cunha-Filho; Ricardo N. Marreto; Stephânia F. Taveira (Drug Delivery and Translational Research, 2022)

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

Metformin effect in models of inflammation is associated with activation of ATP-dependent potassium channels and inhibition of tumor necrosis factor-α production - Paulo S. A. Augusto; Tamires C. Matsui; Alysson V. Braga; Felipe F. Rodrigues; Marcela I. Morais; Marcela M. G. B. Dutra; Carla R. A. Batista; Ivo S. F. Melo; Sarah O. A. M. Costa; Caryne M. Bertollo; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice - Renata L. de Oliveira; Guilherme T. Voss; Karline da C. Rodrigues; Mikaela P. Pinz; Julia V. Biondi; Nicole P. Becker; Eduardo Blodorn; William B. Domingues; Allya Larroza; Vinícius F. Campos; Diego Alves; Ethel A. Wilhelm; et al. (Psychopharmacology, 2022)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Correction to: Seismic fragility functions for Portuguese RC precast buildings - R. Sousa; N. Batalha; V. Silva; H. Rodrigues (Bulletin of Earthquake Engineering, 2021)

Seismic fragility functions for Portuguese RC precast buildings - R. Sousa; N. Batalha; V. Silva; H. Rodrigues (Bulletin of Earthquake Engineering, 2021)

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Chronic exposure to volcanic gaseous elemental mercury: using wild Mus musculus to unveil its uptake and fate - R. Camarinho; A. Navarro-Sempere; P. V. Garcia; M. García; Y. Segovia; A. S. Rodrigues (Environmental Geochemistry and Health, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Total and Organic Mercury in Fish from Different Geographical Areas in the North Atlantic Ocean and Health Risk Assessment - H. C. Vieira; M. M. B. Ramirez; M. D. Bordalo; A. C. M. Rodrigues; A. M. V. M. Soares; S. N. Abreu; F. Morgado; J. Rendón-von Osten (Exposure and Health, 2021)

Mercury Accumulation and Elimination in Different Tissues of Zebrafish (Danio rerio) Exposed to a Mercury-Supplemented Diet - Hugo C. Vieira; Andreia C. M. Rodrigues; Amadeu M. V. M. Soares; Sizenando Abreu; Fernando Morgado (Journal of Marine Science and Engineering, 2021)
In this study, we evaluated the bioaccumulation of mercury in zebrafish (Danio rerio) exposed to mercury-contaminated food for 21 days and the depuration of mercury for a subsequent post-exposure period of 28 days. Four tissues (muscle, liver, gills, and skin) were analyzed for mercury content. Overall, data indicated that Hg accumulation in the liver is faster than in other tissues. Furthermore, the liver is the tissue with the highest accumulation rate per day (0.021 µg Hg g−1 day−1), followed by muscle, skin, and gills. Conversely, the Hg depuration rates in different tissues showed the following order: gills > skin > muscle > liver. The bioaccumulation factor values of liver and muscle increased linearly during the uptake period. The ratios between mercury concentration in liver and muscle during the experiment also increased during the uptake period and remained higher than 1 during the elimination period, suggesting that Danio rerio needed more than 4 weeks of depuration. Finally, the distribution of Hg in the water column during the accumulation period is Hg particulate > Hg dissolved, and during the depuration period it is the opposite, mercury particulate

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

A Concise Review on Induced Pluripotent Stem Cell-Derived Cardiomyocytes for Personalized Regenerative Medicine - Pallavi Pushp; Diogo E. S. Nogueira; Carlos A. V. Rodrigues; Frederico C. Ferreira; Joaquim M. S. Cabral; Mukesh Kumar Gupta (Stem Cell Reviews and Reports, 2021)

Soybean seed chemical treatment associated with inoculants: physiological and agronomical analyses - V. M. Santos; T. C. Oliveira; M. G. Mendes; C. H. Yamanaka; Willian Rodrigues Macedo (Plant Physiology Reports, 2021)

Peptide fraction from latex of Calotropis procera exhibits antifungal and insecticidal activities - Jackson L. Amaral; Cleverson D. T. Freitas; João P. V. Rodrigues; Ghulam Hussain; Márcio V. Ramos; Pedro F. N. Souza (Arthropod-Plant Interactions, 2021)

Human-modified landscapes narrow the isotopic niche of neotropical birds - Ana Beatriz Navarro; Marcelo Magioli; Juliano André Bogoni; Marcelo Zacharias Moreira; Luís Fábio Silveira; Eduardo Roberto Alexandrino; Daniela Tomasio Apolinario da Luz; Marco Aurelio Pizo; Wesley Rodrigues Silva; Vanessa Cristina de Oliveira; Reginaldo José Donatelli; Alexander V. Christianini; et al. (Oecologia, 2021)

Neuronal activity regulated pentraxin (narp) and GluA4 subunit of AMPA receptor may be targets for fluoxetine modulation - Isabella A. Heinrich; Andiara E. Freitas; Ingrid A. V. Wolin; Ana Paula M. Nascimento; Roger Walz; Ana Lúcia S. Rodrigues; Rodrigo B. Leal (Metabolic Brain Disease, 2021)

Physical exercise prevents amyloid β1−40-induced disturbances in NLRP3 inflammasome pathway in the hippocampus of mice - Julia M. Rosa; Anderson Camargo; Ingrid A. V. Wolin; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Survival strategies on a semi-arid island: submersion and desiccation tolerances of fiddler crabs from the Galapagos Archipelago - Mariana V. Capparelli; Carl L. Thurman; Paloma Gusso Choueri; Denis Moledo de Souza Abessa; Mayana Karoline Fontes; Caio Rodrigues Nobre; John Campbell McNamara (Marine Biology, 2021)

First record on mercury accumulation in mice brain living in active volcanic environments: a cytochemical approach - A. Navarro-Sempere; Y. Segovia; A. S. Rodrigues; P. V. Garcia; R. Camarinho; M. García (Environmental Geochemistry and Health, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Sulfate removal from mine-impacted water by electrocoagulation: statistical study, factorial design, and kinetics - Caroline Rodrigues; Hioná V. Dal Magro Follmann; Dámaris Núñez-Gómez; Maria Eliza Nagel-Hassemer; Flávio R. Lapolli; María Ángeles Lobo-Recio (Environmental Science and Pollution Research, 2020)

Costus stripe mosaic virus, a tentative new member of the genus Potyvirus - M. Amelia V. Alexandre; Ligia M. L. Duarte; Pedro L. Ramos-González; Alexandre L. R. Chaves; Ricardo Harakava; Leilane K. Rodrigues; Camila Chabi-Jesus; E. W. Kitajima (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Melaleuca leucadendra Essential Oil Promotes Loss of Cell Membrane and Wall Integrity and Inhibits Bacterial Growth: An In Silico and In Vitro Approach - Jessica P. Bautista-Silva; Janaína B. Seibert; Tatiane R. Amparo; Ivanildes V. Rodrigues; Luiz Fernando M. Teixeira; Gustavo Henrique B. Souza; Orlando D. H. dos Santos (Current Microbiology, 2020)

Evaluation of gully development over several years using GIS and fractal analysis: a case study of the Palmital watershed, Minas Gerais (Brazil) - L. S. C. Real; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2020)

Natural Enemies of the Harrisia Cactus Mealybug and Other Hypogeococcus Species (Hemiptera: Pseudococcidae) in Puerto Rico: Identification and Taxonomic Notes on Primary and Secondary Parasitoids - S. V. Triapitsyn; S. D. Hight; G. A. Logarzo; M. B. Aguirre; J. C. Verle Rodrigues; V. A. Trjapitzin; Z. Rivera Ocasio; M. L. Rivera-Vázquez; M. J. West Ortiz; Y. Rodríguez Reyes (Neotropical Entomology, 2020)

The oviposition behavior of fall armyworm moths is unlikely to compromise the refuge strategy in genetically modified Bt crops - Jaciara Gonçalves; João Victor C. Rodrigues; Oscar F. Santos-Amaya; Silvana V. Paula-Moraes; Eliseu José G. Pereira (Journal of Pest Science, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Running to the mountains: mammal species will find potentially suitable areas on the Andes - Cleide Carnicer; Pedro V. Eisenlohr; Anah Tereza de Almeida Jácomo; Leandro Silveira; Giselle Bastos Alves; Natália Mundim Tôrres; Fabiano Rodrigues de Melo (Biodiversity and Conservation, 2020)

Clindamycin inhibits nociceptive response by reducing tumor necrosis factor-α and CXCL-1 production and activating opioidergic mechanisms - Felipe F. Rodrigues; Marcela I. Morais; Ivo S. F. Melo; Paulo S. A. Augusto; Marcela M. G. B. Dutra; Sarah O. A. M. Costa; Fábio C. Costa; Franciele A. Goulart; Alysson V. Braga; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Evidence of strong population bottleneck in genetics of endangered Brazilian Merganser (Mergus octosetaceus) - T. A. Maia; D. P. Campos; L. R. Silva; L. V. Lins; F. Ribeiro; F. Sebaio; F. R. Rodrigues; G. P. M. Dantas (Journal of Ornithology, 2020)

Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome - Jéssica A. M. Rodrigues; Marcelo R. Viola; Lívia A. Alvarenga; Carlos R. de Mello; Sin C. Chou; Vinícius A. de Oliveira; Venkatesh Uddameri; Marco A. V. Morais (International Journal of Climatology, 2020)
Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the HadGEM2‐ES and MIROC5 global climate models associated with RCP4.5 and RCP8.5 scenarios were used in three time slices (2011–2040, 2041–2070 and 2071–2099). The Standardized Precipitation Index (SPI) and the Standardized Streamflow Index (SSFI) were used to characterize droughts. In general, the results showed that the duration, intensity and frequency of the meteorological and hydrological droughts are expected to increase during the future periods. However, the hydrological droughts are projected to be larger than the meteorological droughts. Reductions in the streamflow are indicated in all future time slices and under both RCPs, especially, during dry periods, which may cause negative impacts in the ecological functions of the Cerrado biome, risk for reduction of the recharge of aquifers and risk for the electric energy production in northern Brazil.

Deleterious effects of chronic mercury exposure on in vitro LTP, memory process, and oxidative stress - Leandro F. Oliveira; Laís D. Rodrigues; Giancarlo M. Cardillo; Mariana B. Nejm; Marcia Guimarães-Marques; Selvin Z. Reyes-Garcia; Karolini Zuqui; Dalton V. Vassallo; Ana C. Fiorini; Carla A. Scorza; Fulvio A. Scorza (Environmental Science and Pollution Research, 2020)

Thiamine, riboflavin, and nicotinamide inhibit paclitaxel-induced allodynia by reducing TNF-α and CXCL-1 in dorsal root ganglia and thalamus and activating ATP-sensitive potassium channels - Alysson V. Braga; Sarah O. A. M. Costa; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela I. Morais; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Will the emblematic southern conifer Araucaria angustifolia survive to climate change in Brazil? - Monik Begname Castro; Ana Carolina Maioli Campos Barbosa; Patrícia Vieira Pompeu; Pedro V. Eisenlohr; Gabriel de Assis Pereira; Deborah Mattos Guimarães Apgaua; João Carlos Pires-Oliveira; João Paulo Rodrigues Alves Delfino Barbosa; Marco Aurélio Leite Fontes; Rubens Manoel dos Santos; David Yue Phin Tng (Biodiversity and Conservation, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Physiological and biochemical responses of soybean to white mold affected by manganese phosphite and fluazinam - M. I. C. Novaes; D. Debona; I. R. F. Fagundes-Nacarath; V. V. Brás; F. A. Rodrigues (Acta Physiologiae Plantarum, 2019)

Noninferiority field trial for evaluation of efficacy of ciprofloxacin associated with internal teat sealant as dry-off protocol - Cristian Marlon de Magalhães Rodrigues Martins; Bruna Gomes Alves; Camylla Pedrosa Monteiro; Eduardo Souza Campos Pinheiro; Marcelo Arne Feckinghaus; Luiz Gustavo Paranhos; Marcos V. dos Santos (Tropical Animal Health and Production, 2019)

Effects of ammoniated pearl millet silage on intake, feeding behavior, and blood metabolites in feedlot lambs - Thomaz C. G. de C. Rodrigues; Poliane M. Freitas; Edson M. Santos; Gherman G. L. de Araújo; Aureliano J. V. Pires; Maria C. C. Ayres; Lorendane M. de Carvalho; Jocely G. Souza; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Skeletal muscle miR-34a/SIRT1:AMPK axis is activated in experimental and human non-alcoholic steatohepatitis - André L. Simão; Marta B. Afonso; Pedro M. Rodrigues; Margarida Gama-Carvalho; Mariana V. Machado; Helena Cortez-Pinto; Cecília M. P. Rodrigues; Rui E. Castro (Journal of Molecular Medicine, 2019)

Chemical Characterization and Biotechnological Applicability of Pigments Isolated from Antarctic Bacteria - Tiago R. Silva; Renata S. N. Tavares; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Iramaia A. Neri-Numa; Glaucia M. Pastore; Luiz H. Rosa; José A. A. Schultz; Hosana M. Debonsi; Lorena R. G. Cordeiro; Valeria M. Oliveira (Marine Biotechnology, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Pigments in an iridescent bacterium, Cellulophaga fucicola, isolated from Antarctica - Tiago R. Silva; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Fábio N. dos Santos; Marcos N. Eberlin; Iramaia A. Neri-Numa; Glaucia M. Pastore; Renata S. N. Tavares; Hosana M. Debonsi; Lorena R. G. Cordeiro; Luiz H. Rosa; et al. (Antonie van Leeuwenhoek, 2019)

Pleistocene alkaline rocks of Martin Vaz volcano, South Atlantic: low-degree partial melts of a CO 2 -metasomatized mantle plume - Anderson C. Santos; Mauro C. Geraldes; Wolfgang Siebel; Julio Mendes; Everton Bongiolo; Werlem H Santos; Thais C. V. Garrido; Sergio W. O. Rodrigues (International Geology Review, 2019)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Lagged Population Growth in a Termite Host Colony: Cause or Consequence of Inquilinism? - V B Rodrigues; D A Costa; P F Cristaldo; O DeSouza (Neotropical Entomology, 2018)

Risk Assessment of the Drinking Water Samples in the Rural Area from MG, Brazil - Mayra S. Santos; Maria C. R. M. Metzker; Guilherme L. Rodrigues; Luis R. S. Corrêa; Mayne L. V. Silva; Ana L. G. Barbosa; Márcia C. S. Faria; Jairo L. Rodrigues (International Journal of Environmental Research, 2018)

Soluble Compounds of Filamentous Fungi Harm the Symbiotic Fungus of Leafcutter Ants - Rodolfo Bizarria; Isabela C. Moia; Quimi V. Montoya; Danilo A. Polezel; Andre Rodrigues (Current Microbiology, 2018)

Phosphites attenuate Sclerotinia sclerotiorum-induced physiological impairments in common bean - I. R. F. Fagundes-Nacarath; D. Debona; V. V. Brás; P. R. Silveira; F. A. Rodrigues (Acta Physiologiae Plantarum, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Evaluation of different samplers and storage temperature effect on the methane carbon stable isotope analysis - Victor H. J. M. dos Santos; Diane O. Laroque; Caroline I. Baum; Pâmela de M. Engelmann; Rogério V. Lourega; Luiz F. Rodrigues (Environmental Monitoring and Assessment, 2018)

Histopathological Evaluation of Combined Impacts of the Synthetic Progestin Levonorgestrel and Temperature on the Female Zebrafish Maturation Using a Semi-quantitative Grading Analysis—Is it Enough? - P. G. Cardoso; D. Rodrigues; T. V. Madureira; M. J. Rocha; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2018)

Combined effects of insecticide exposure and predation risk on freshwater detritivores - Andreia C. M. Rodrigues; Maria D. Bordalo; Oksana Golovko; Olga Koba; Carlos Barata; Amadeu M. V. M. Soares; João L. T. Pestana (Ecotoxicology, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya - Johana Madroñero; Silas P. Rodrigues; Tathiana F. S. Antunes; Paolla M. V. Abreu; José A. Ventura; A. Alberto R. Fernandes; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Lepeophtheirus azoricus n. sp. (Copepoda: Caligidae) parasitic on dusky grouper, Epinephelus marginatus, from Atlantic waters off the Azores, Portugal - Argun Akif Özak; Alfredo M. V. Rodrigues; Nina S. S. Vieira; Rui M. G. Rosa; Alper Yanar; Erkin Koyuncu; Geoffrey A. Boxshall (Marine Biodiversity, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

New cytotoxic furan from the marine sediment-derived fungi Aspergillus niger - Paula Karina S. Uchoa; Antonia T. A. Pimenta; Raimundo Braz-Filho; Maria da Conceição F. de Oliveira; Natália N. Saraiva; Barbara S. F. Rodrigues; Ludwig H. Pfenning; Lucas M. Abreu; Diego V. Wilke; Katharine G. D. Florêncio; Mary Anne S. Lima (Natural Product Research, 2017)

Structural equation modeling for the estimation of interconnections between the P cycle and soil properties - Marcus V. S. Sales; Seldon Aleixo; Antonio Carlos Gama-Rodrigues; Emanuela Forestieri Gama-Rodrigues (Nutrient Cycling in Agroecosystems, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

N-acylhydrazones containing thiophene nucleus: a new anticancer class - Laura N. F. Cardoso; Thais C. M. Nogueira; Felipe A. R. Rodrigues; Augusto Cesar Aragão Oliveira; Maria Claudia dos Santos Luciano; Claudia Pessoa; Marcus V. N. de Souza (Medicinal Chemistry Research, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Erratum to: Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Application of solar photo-Fenton toward toxicity removal and textile wastewater reuse - Maria Clara V. M. Starling; Paulo Henrique Rodrigues dos Santos; Felipe Antônio Ribeiro de Souza; Sílvia Corrêa Oliveira; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Benthic dinoflagellate blooms in tropical intertidal rock pools: elucidation of photoprotection mechanisms - J. S. Patil; R. V. Rodrigues; P. Paul; K. Sathish; M. Rafi; A. C. Anil (Marine Biology, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Exploring 1,2,3-triazole derivatives by using in vitro and in silico assays to target new antifungal agents and treat Candidiasis - Taísa F. Santos; Jéssica B. de Jesus; Paulo M. Neufeld; Alessandro K. Jordão; Vinícius R. Campos; Anna C. Cunha; Helena C. Castro; Maria C. B. V. de Souza; Vitor F. Ferreira; Carlos R. Rodrigues; Paula A. Abreu (Medicinal Chemistry Research, 2017)

Synthesis, antimicrobial activity and cytotoxic investigation of novel trifluoromethylated tetrazolo[1,5-a]pyrimidines - Elisandra Scapin; Clarissa P. Frizzo; Leticia V. Rodrigues; Geórgia C. Zimmer; Rodrigo A. Vaucher; Michelle R. Sagrillo; Janice L. Giongo; Carlos A. M. Afonso; Patrícia Rijo; Nilo Zanatta; Helio G. Bonacorso; Marcos A. P. Martins (Medicinal Chemistry Research, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

“Why throw away something useful?”: Attitudes and opinions of people treated for bipolar disorder and their relatives on organ and tissue donation - Carolina S. Padoan; Lucas F. Garcia; Aline A. Rodrigues; Lucas M. Patusco; Mariana V. Atz; Flavio Kapczinski; José R. Goldim; Pedro V. S. Magalhães (Cell and Tissue Banking, 2017)

A method for collecting eggs of Pseudocapillaria tomentosa (Nematoda: Capillariidae) from zebrafish Danio rerio and efficacy of heat and chlorine for killing the nematode's eggs - M L Martins; V Watral; J P Rodrigues‐Soares; M L Kent (Journal of Fish Diseases, 2017)
Pseudocapillaria tomentosa is a common pathogen of zebrafish ( Danio rerio ) in research facilities. We developed a method to collect and concentrate the nematode eggs using a modified sugar centrifugation method and documented their normal development. Embryonating stages with blastomere formation followed by elongation of the embryo prior to larva formation cumulated in developed larvae inside the eggs and hatching after 5–10 day. We then evaluated the efficacy of heat and chlorine to kill them based on a larva development assay. Eggs were exposed to 40, 50, 60 °C for 30 min and 1 h. Chlorine treatment was performed at 100, 250, 500, 1000, 3000 and 6000 ppm for 10 min. Samples exposed to 40 °C for 30 min or 1 h showed incidences of larvated eggs similar to controls. In contrast, no larvation occurred with eggs exposed to either 50 or 60 °C for 30 min or 1 h. Remarkably, in repeated assays, samples exposed to low doses of chlorine (100, 250, 500 and 1000 ppm for 10 min) showed significantly higher incidence of larvation than controls. Eggs treated with 3000 ppm for 10 min did not develop larvae, and no eggs were found after 6000 ppm treatment.

Multibiomarker responses in aquatic insect Belostoma elegans (Hemiptera) to organic pollution in freshwater system - S. Lavarías; C. Ocon; V. López van Oosterom; A. Laino; D. A. Medesani; A. Fassiano; H. Garda; J. Donadelli; M. Ríos de Molina; A. Rodrigues Capítulo (Environmental Science and Pollution Research, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Essential oils to control ichthyophthiriasis in pacu, Piaractus mesopotamicus (Holmberg): special emphasis on treatment with Melaleuca alternifolia - G M R Valladão; S U Gallani; C V Ikefuti; C da Cruz; N Levy‐Pereira; M V N Rodrigues; F Pilarski (Journal of Fish Diseases, 2016)
In vitro effect of the Melaleuca alternifolia , Lavandula angustifolia and Mentha piperita essential oils ( EO s) against Ichthyophthirius multifiliis and in vivo effect of M. alternifolia for treating ichthyophthiriasis in one of the most important South American fish, Piaractus mesopotamicus (Holmberg), were evaluated. The in vitro test consisted of three EO s, each at concentrations of 57 μL L −1 , 114 μL L −1 , 227 μL L −1 and 455 μL L −1 , which were assessed once an hour for 4 h in microtitre plates (96 wells). The in vitro results demonstrated that all tested EO s showed a cytotoxic effect against I. multifiliis compared to control groups ( P 0.05). The in vivo treatment for white spot disease was performed in a bath for 2 h day −1 for 5 days using the M. alternifolia EO (50 μL L −1 ). In this study, 53.33% of the fish severely infected by I. multifiliis survived after the treatment with M. alternifolia (50 μL L −1 ) and the parasitological analysis has shown an efficacy of nearly 100% in the skin and gills, while all the fish in the control group died. Furthermore, the potential positive effect of M. alternifolia EO against two emergent opportunistic bacteria in South America Edwardsiella tarda and Citrobacter freundii was discussed.

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Genetic pool structure of local apple cultivars from Portugal assessed by microsatellites - V. Ferreira; A. M. Ramos-Cabrer; V. Carnide; O. Pinto-Carnide; A. Assunção; A. Marreiros; R. Rodrigues; S. Pereira-Lorenzo; I. Castro (Tree Genetics & Genomes, 2016)

Comparison of UV photolysis, nanofiltration, and their combination to remove hormones from a drinking water source and reduce endocrine disrupting activity - Sandra Sanches; Alexandre Rodrigues; Vitor V. Cardoso; Maria J. Benoliel; João G. Crespo; Vanessa J. Pereira (Environmental Science and Pollution Research, 2016)

Leaf gas exchange and multiple enzymatic and non-enzymatic antioxidant strategies related to drought tolerance in two oil palm hybrids - Priscilla A. Silva; Igor V. Oliveira; Kátia C. B. Rodrigues; Vanessa S. Cosme; Abel J. R. Bastos; Kelly S. C. Detmann; Roberto L. Cunha; Reginaldo A. Festucci-Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Trees, 2016)

A novel N-acetyl-glucosamine lectin of Lonchocarpus araripensis attenuates acute cellular inflammation in mice - Alana F. Pires; Natália V. F. C. Rodrigues; Pedro Marcos G. Soares; Ronaldo de Albuquerque Ribeiro; Karoline S. Aragão; Márcia M. Marinho; Mayara T. L. da Silva; Benildo S. Cavada; Ana Maria S. Assreuy (Inflammation Research, 2016)

Characterization of antiproliferative potential and biological targets of a copper compound containing 4′-phenyl terpyridine - Ana Soraia Mendo; Sara Figueiredo; Catarina Roma-Rodrigues; Paula A. Videira; Zhen Ma; Mário Diniz; Miguel Larguinho; Pedro M. Costa; João C. Lima; Armando J. L. Pombeiro; Pedro V. Baptista; Alexandra R. Fernandes (JBIC Journal of Biological Inorganic Chemistry, 2015)

Cytotoxic compounds from the marine-derived fungus Aspergillus sp. recovered from the sediments of the Brazilian coast - Natália N. Saraiva; Bárbara S.F. Rodrigues; Paula C. Jimenez; Larissa A. Guimarães; Maria C.M. Torres; Edson Rodrigues-Filho; Ludwig H. Pfenning; Lucas M. Abreu; Jair Mafezoli; Marcos C. de Mattos; Letícia V. Costa-Lotufo; Maria da Conceição F. de Oliveira (Natural Product Research, 2015)

Respecification of structural equation models for the P cycle in tropical soils - M. V. S. Sales; A. C. Gama-Rodrigues; N. B. Comerford; W. P. Cropper; E. F. Gama-Rodrigues; P. H. G. Oliveira (Nutrient Cycling in Agroecosystems, 2015)

Iron loading site on the Fe–S cluster assembly scaffold protein is distinct from the active site - Andria V. Rodrigues; Ashoka Kandegedara; John A. Rotondo; Andrew Dancis; Timothy L. Stemmler (BioMetals, 2015)

Occurrence and analysis of endocrine-disrupting compounds in a water supply system - A. R. M Carvalho; V. V. Cardoso; A. Rodrigues; E. Ferreira; M. J. Benoliel; E. A. Duarte (Environmental Monitoring and Assessment, 2015)

Evaluation of (2S,3R)-2-(amino)-[4-(N-benzylarenesulfonamido)-3-hydroxy-1-phenylbutane derivatives: a promising class of anticancer agents - Victor Facchinetti; Marcele Moreth; Claudia R. B. Gomes; Cláudia do Ó Pessoa; Felipe A. R. Rodrigues; Bruno C. Cavalcanti; Augusto C. A. Oliveira; Teiliane R. Carneiro; Ivson Lelis Gama; Marcus V. N. de Souza (Medicinal Chemistry Research, 2015)

Oysters as hot spots for mimivirus isolation - Kétyllen R. Andrade; Paulo P. V. M. Boratto; Felipe P. Rodrigues; Lorena C. F. Silva; Fábio P. Dornas; Mariana R. Pilotto; Bernard La Scola; Gabriel M. F. Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Population dynamics of Aceodromus convolvuli (Acari: Mesostigmata: Blattisociidae) on spontaneous plants associated with Jatropha curcas in central Brazil - Wilton P. Cruz; Renato A. Sarmento; Marçal Pedro-Neto; Adenir V. Teodoro; Diego M. Rodrigues; Gilberto J. de Moraes (Experimental and Applied Acarology, 2014)

Nutrient stocks in litterfall and litter in cocoa agroforests in Brazil - A. G. Fontes; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. V. S. Sales; M. G. Costa; R. C. R. Machado (Plant and Soil, 2014)

A Clinico-Mycological Study of Dermatophytoses in Goa, India - Saleel V. Maulingkar; M. J. W. Pinto; S. Rodrigues (Mycopathologia, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Alterations in the extracellular catabolism of nucleotides and platelet aggregation induced by high-fat diet in rats: effects of α-tocopherol - Jessié M. Gutierres; Fabiano B. Carvalho; Maria Rosa C. Schetinger; Marília V. Rodrigues; Juliano M. Vieira; Paula Maldonado; Maria do Carmo S. Araújo; Roberta Schmatz; Naiara Stefanello; Jeandre A. S. Jaques; Marcio Costa; Vera Morsch; et al. (Journal of Physiology and Biochemistry, 2014)

A poly-ε-caprolactone based biofilm carrier for nitrate removal from water - A. L. Rodrigues; A. V. Machado; J. M. Nóbrega; A. Albuquerque; A. G. Brito; R. Nogueira (International Journal of Environmental Science and Technology, 2014)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Phylogeography and genetic diversity of the Robin (Erithacus rubecula) in the Azores Islands: Evidence of a recent colonisation - Pedro Rodrigues; Ricardo Jorge Lopes; Sergei V. Drovetski; Sandra Reis; Jaime A. Ramos; Regina Tristão da Cunha (Journal of Ornithology, 2013)

Evaluating the fidelity of downscaled climate data on simulated wheat and maize production in the southeastern US - Davide Cammarano; Lydia Stefanova; Brenda V. Ortiz; Melissa Ramirez-Rodrigues; Senthold Asseng; Vasubandhu Misra; Gail Wilkerson; Bruno Basso; James W. Jones; Kenneth J. Boote; Steven DiNapoli (Regional Environmental Change, 2013)

Biological impacts of ocean acidification: a postgraduate perspective on research priorities - Samantha L. Garrard; R. C. Hunter; A. Y. Frommel; A. C. Lane; J. C. Phillips; R. Cooper; R. Dineshram; U. Cardini; S. J. McCoy; M. Arnberg; B. G. Rodrigues Alves; S. Annane; et al. (Marine Biology, 2013)

Mercury Toxicity to Freshwater Organisms: Extrapolation Using Species Sensitivity Distribution - Andreia C. M. Rodrigues; Fátima T. Jesus; Marco A. F. Fernandes; Fernando Morgado; Amadeu M. V. M. Soares; Sizenando N. Abreu (Bulletin of Environmental Contamination and Toxicology, 2013)

In vitro exploration of potential mechanisms of toxicity of the human hepatotoxic drug fenclozic acid - Alison V. M. Rodrigues; Helen E. Rollison; Scott Martin; Sunil Sarda; Timothy Schulz-Utermoehl; Simone Stahl; Frida Gustafsson; Julie Eakins; J. Gerry Kenna; Ian D. Wilson (Archives of Toxicology, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Chemical composition and in vitro schistosomicidal activity of the essential oil from the flowers of Bidens sulphurea (Asteraceae) - G.P. Aguiar; N.I. Melo; K.A.L. Wakabayashi; M.H.S. Lopes; A.L.L. Mantovani; H.J. Dias; M.J. Fukui; L.C. Keles; V. Rodrigues; M. Groppo; A.A. Silva-Filho; W.R. Cunha; et al. (Natural Product Research, 2013)

Genetic and QTL analyses of yield and a set of physiological traits in pepper - N. A. Alimi; M. C. A. M. Bink; J. A. Dieleman; M. Nicolaï; M. Wubs; E. Heuvelink; J. Magan; R. E. Voorrips; J. Jansen; P. C. Rodrigues; G. W. A. M. van der Heijden; A. Vercauteren; et al. (Euphytica, 2013)

Contrasting egg and larval performances help explain polyphagy in a florivorous butterfly - Daniela Rodrigues; André V. L. Freitas (Arthropod-Plant Interactions, 2013)

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil - Andréia Dalla Vecchia; Mariana Kluge; Joseane V. dos Santos da Silva; Juliana Comerlato; Manoela T. Rodrigues; Juliane D. Fleck; Roger B. da Luz; Thais F. Teixeira; Paulo M. Roehe; Roberta Capalonga; Ana Beatriz Oliveira; Fernando R. Spilki (Food and Environmental Virology, 2013)

Organic solutes in the deepest phylogenetic branches of the Bacteria: identification of α(1–6)glucosyl-α(1–2)glucosylglycerate in Persephonella marina - Pedro Lamosa; Marta V. Rodrigues; Luís G. Gonçalves; Jean Carr; Rita Ventura; Christopher Maycock; Neil D. Raven; Helena Santos (Extremophiles, 2013)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Carbon, nitrogen, organic phosphorus, microbial biomass and N mineralization in soils under cacao agroforestry systems in Bahia, Brazil - F. C. Zaia; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. K. S. Moço; A. G. Fontes; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2012)

Immunological Aspects in Amyotrophic Lateral Sclerosis - Maria Carolina O. Rodrigues; Júlio C. Voltarelli; Paul R. Sanberg; Cesario V. Borlongan; Svitlana Garbuzova-Davis (Translational Stroke Research, 2012)

Influence of soil water content and atmospheric conditions on leaf water potential in cv. “Touriga Nacional” deep-rooted vineyards - P. Rodrigues; V. Pedroso; J. P. Gouveia; S. Martins; C. Lopes; I. Alves (Irrigation Science, 2012)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Spatial distributions of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) on coconut and their implications for development of efficient sampling plans - A. Roda; G. Nachman; F. Hosein; J. C. V. Rodrigues; J. E. Peña (Experimental and Applied Acarology, 2012)

A review of the natural enemies of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) - Daniel Carrillo; J. Howard Frank; Jose Carlos V. Rodrigues; Jorge E. Peña (Experimental and Applied Acarology, 2012)

An electronic study of pyrazolones drugs on agranulocytosis - J. Rodrigues Silva; A. Noronha Queiroz; E. A. Fontes Junior; M. V. Santos Silva; A. Manoel Herculano; A. M. J. Chaves Neto; R. Santos Borges (Medicinal Chemistry Research, 2012)

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development - Isadora Machado T. Lima; Ivina R. Brito; Rafael Rossetto; Ana Beatriz G. Duarte; Giovanna Q. Rodrigues; Márcia Viviane A. Saraiva; José Jackson N. Costa; Mariana Aragão M. Donato; Christina A. Peixoto; José Roberto V. Silva; José Ricardo de Figueiredo; Ana Paula R. Rodrigues (Cell and Tissue Research, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Ultrastructural changes during early infection of Vigna unguiculata and Phaseolus vulgaris leaves by Xanthomonas axonopodis pv. phaseoli and an unexpected association between chloroplast and mitochondrion - André de O. Carvalho; Maura Da Cunha; Rosana Rodrigues; Cláudia P. Sudré; Izabela S. Santos; Kátia V. S. Fernandes; Guilherme R. Rabelo; Valdirene M. Gomes (Acta Physiologiae Plantarum, 2011)

A new race of Puccinia psidii defeats rust resistance in eucalypt - Rodrigo N. Graça; Cristina P. Aun; Lúcio M. S. Guimarães; Bruno V. A. Rodrigues; Edival A. V. Zauza; Acelino C. Alfenas (Australasian Plant Pathology, 2011)

Alterations on rice leaf physiology during infection by Bipolaris oryzae - Leandro J. Dallagnol; Fabrício A. Rodrigues; Samuel C. V. Martins; Paulo C. Cavatte; Fábio M. DaMatta (Australasian Plant Pathology, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Suitability of the predatory mites Iphiseiodes zuluagai and Euseius concordis in controlling Polyphagotarsonemus latus and Tetranychus bastosi on Jatropha curcas plants in Brazil - Renato Almeida Sarmento; Diego Macedo Rodrigues; Farid Faraji; Eduardo A. L. Erasmo; Felipe Lemos; Adenir V. Teodoro; Wagner Toshihiro Kikuchi; Gil Rodrigues dos Santos; Angelo Pallini (Experimental and Applied Acarology, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

The use of Daphnia magna immobilization tests and soil microcosms to evaluate the toxicity of dredged sediments - Ana F. Pereira Miranda; José M. L. Rodrigues; Carlos Barata; Carmen Riva; Dayanthi Nugegoda; Amadeu M. V. M. Soares (Journal of Soils and Sediments, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Wheat resistance to leaf blast mediated by silicon - M. S. Xavier Filha; F. A. Rodrigues; G. P. Domiciano; H. V. Oliveira; P. R. Silveira; W. R. Moreira (Australasian Plant Pathology, 2011)

Intake and digestibility in cattle fed low-quality tropical forage and supplemented with nitrogenous compounds - Claudia B. Sampaio; Edenio Detmann; Mario F. Paulino; Sebastiao C. Valadares Filho; Marjorrie A. de Souza; Isis Lazzarini; Pedro V. Rodrigues Paulino; Augusto C. de Queiroz (Tropical Animal Health and Production, 2010)

Molecular markers for the DNA fingerprinting of Paphiopedilum dayanum and Paphiopedilum lowii, two endangered slipper orchids - K. F. Rodrigues; Z. A. Aziz; S. V. Kumar; M. A. Latip (Conservation Genetics Resources, 2010)

Trade-offs underlying polyphagy in a facultative ant-tended florivorous butterfly: the role of host plant quality and enemy-free space - Daniela Rodrigues; Lucas A. Kaminski; André V. L. Freitas; Paulo S. Oliveira (Oecologia, 2010)

Characterization of two recessive genes controlling resistance to all races of bacterial spot in peppers - C. Eduardo Vallejos; Valerie Jones; Robert E. Stall; Jeffrey B. Jones; Gerald V. Minsavage; Diana C. Schultz; Rosana Rodrigues; Lisa E. Olsen; Michael Mazourek (Theoretical and Applied Genetics, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Horizontal nutrient fluxes and food safety in urban and peri-urban vegetable and millet cultivation of Niamey, Niger - Rodrigue V. C. Diogo; Andreas Buerkert; Eva Schlecht (Nutrient Cycling in Agroecosystems, 2010)

Mappings between a macroscopic neural-mass model and a reduced conductance-based model - Serafim Rodrigues; Anton V. Chizhov; Frank Marten; John R. Terry (Biological Cybernetics, 2010)

Water relations and chlorophyll fluorescence responses of two leguminous trees from the Caatinga to different watering regimes - Bruna D. Souza; Marcos V. Meiado; Bruno M. Rodrigues; Mauro G. Santos (Acta Physiologiae Plantarum, 2010)

Isolation and characterization of microsatellite loci in Phalaenopsis gigantea - K. F. Rodrigues; S. V. Kumar (Conservation Genetics, 2009)

Conservation of dual-targeted proteins in Arabidopsis and rice points to a similar pattern of gene-family evolution - Carolina V. Morgante; Ricardo A. O. Rodrigues; Phellippe A. S. Marbach; Camila M. Borgonovi; Daniel S. Moura; Marcio C. Silva-Filho (Molecular Genetics and Genomics, 2009)

Soil and litter fauna of cacao agroforestry systems in Bahia, Brazil - M. K. da Silva Moço; E. F. da Gama-Rodrigues; A. C. da Gama-Rodrigues; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2009)

Temperature-dependent development rates of Bracon vulgaris, a parasitoid of boll weevil - F. S. Ramalho; P. A. Wanderley; J. B. Malaquias; K. C. V. Rodrigues; J. V. S. Souza; J. C. Zanuncio (Phytoparasitica, 2009)

Isolation and characterization of 24 microsatellite loci in Paphiopedilum rothschildianum, an endangered slipper orchid - K. F. Rodrigues; S. V. Kumar (Conservation Genetics, 2009)

Effect of root and foliar applications of silicon on brown spot development in rice - D. C. Rezende; F. Á. Rodrigues; V. Carré-Missio; D. A. Schurt; I. K. Kawamura; G. H. Korndörfer (Australasian Plant Pathology, 2009)

Purification of polyhydroxybutyrate produced by Burkholderia cepacia IPT64 through a chemical and enzymatic route - Daniel V. Suzuki; José M. Carter; Maria Filomena A. Rodrigues; Elda S. da Silva; Alfredo E. Maiorano (World Journal of Microbiology and Biotechnology, 2008)

Superoxide reduction by Nanoarchaeum equitans neelaredoxin, an enzyme lacking the highly conserved glutamate iron ligand - João V. Rodrigues; Bruno L. Victor; Harald Huber; Lígia M. Saraiva; Cláudio M. Soares; Diane E. Cabelli; Miguel Teixeira (JBIC Journal of Biological Inorganic Chemistry, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Acute toxicity testing with the European estuarine amphipod Corophium multisetosum - Ana Ré; A. M. Rodrigues; V. Quintino (Hydrobiologia, 2007)

Spatial heterogeneity recognition in estuarine intertidal benthic macrofaunal communities: influence of sieve mesh-size and sampling depth - Ana Maria Rodrigues; S. Meireles; T. Pereira; V. Quintino (Hydrobiologia, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Superoxide reduction by Archaeoglobus fulgidus desulfoferrodoxin: comparison with neelaredoxin - João V. Rodrigues; Lígia M. Saraiva; Isabel A. Abreu; Miguel Teixeira; Diane E. Cabelli (JBIC Journal of Biological Inorganic Chemistry, 2007)

Water tank and numerical model studies of flow over steep smooth two-dimensional hills - J. B. R. Loureiro; D. V. Soares; J. L. A. Fontoura Rodrigues; F. T. Pinho; A. P. Silva Freire (Boundary-Layer Meteorology, 2007)

Larval Cryptothelea gloverii (Lepidoptera: Psycidae), an arthropod predator and herbivore on Florida citrus - Raul T. Villanueva; Jose C. V. Rodrigues; Carl C. Childers (Experimental and Applied Acarology, 2005)

Mitochondrial DNA and RAPD polymorphisms in the haploid mite Brevipalpus phoenicis (Acari: Tenuipalpidae) - J. C. V. Rodrigues; M. Gallo-meagher; R. Ochoa; C. C. Childers; B. J. Adams (Experimental and Applied Acarology, 2004)

Identification of differentially expressed cDNA sequences in ovaries of sexual and apomictic plants of Brachiaria brizantha - Júlio C.M. Rodrigues; Gláucia B. Cabral; Diva M.A. Dusi; Luciane V. de Mello; Daniel J. Rigden; Vera T.C. Carneiro (Plant Molecular Biology, 2003)

Impairment of inflammatory response in adult rats submitted to maternal undernutrition during early lactation: Role of insulin and glucocorticoid - C. Barja-Fidalgo; E. P. G. Souza; S. V. Silva; A. L. Rodrigues; E. A. Anjos-Valotta; P. Sannomyia; M. S. DeFreitas; A. S. Moura (Inflammation Research, 2003)

Validation of a more sensitive method for using spotted oligonucleotide DNA microarrays for functional genomics studies on bacterial communities - Vincent J. Denef; Joonhong Park; Jorge L. M. Rodrigues; Tamara V. Tsoi; Syed A. Hashsham; James M. Tiedje (Environmental Microbiology, 2003)
Summary Spotted oligonucleotide microarrays potentially offer a wide scope of applications for microbial ecology, especially as they improve the flexibility of design and the specificity of detection compared to PCR product based microarrays. Sensitivity, however, was expected to be problematic, as studies with the more sensitive PCR‐based cDNA microarrays indicate that only genes from populations contributing to more than 5% of the community DNA can be detected. We evaluated several parameters to increase sensitivity and then tested applicability for bacterial functional genomics. The optimal parameters were the use of 5′‐C6‐amino‐modified 70‐mers printed on CMT‐GAPS II substrates at a 40 µM concentration combined with the use of Tyramide Signal Amplification labelling. This protocol allowed detection of single copy genes belonging to an organism contributing to 1% or more of the total community. To demonstrate its application, we detected the specific aromatic oxygenase genes in a soil community degrading polychlorinated biphenyls (PCBs). This increase in sensitivity is important if oligonucleotide microarrays are to be used for simultaneous monitoring of a range of functions performed by different microorganisms in the environment.

Host Plants of Brevipalpus californicus, B. obovatus, and B. phoenicis (Acari: Tenuipalpidae) and their Potential Involvement in the Spread of Viral Diseases Vectored by these Mites - Carl C. Childers; Jose Carlos V. Rodrigues; Warren C. Welbourn (Experimental and Applied Acarology, 2003)

Brevipalpus californicus, B. obovatus, B. phoenicis, and B. lewisi (Acari: Tenuipalpidae): a Review of their Biology, Feeding Injury and Economic Importance - Carl C. Childers; J. Victor French; Jose Carlos V. Rodrigues (Experimental and Applied Acarology, 2003)

Inorganic nitrogen assimilation by picoplankton and whole plankton in a coastal ecosystem - Rubina M. N. V. Rodrigues; Peter J. le B. Williams (Limnology and Oceanography, 2002)
NH 4 + and NO 3 − seasonal uptake by the phytoplankton and 2 ‐determined primary production and DIN metabolism measurements, five phases were defined: (1) prebloom (before April), (2) primary net autotrophic (April and May), (3) net heterotrophic (June), (4) secondary net autotrophic (July and August), and (5) regenerative (remainder of calendar year). The inorganic N nutrition of phytoplankton and 3 − −based in spring and NH 4 + ‐based in summer and autumn, reflecting varying ambient concentrations of these nutrients superimposed on a general preference for NH 4 + by both communities. The percent contribution of picoplankton to the total NH 4 + uptake was higher than to nitrate (seasonal averages of 50 ± 14% and 32 ± 24%, respectively). The contribution of the 4 + and NO 3 − assimilation by the 3 − and NH 4 + uptake, respectively. In the net heterotrophic phase, it amounted to ca. 70% of the total DIN uptake, with no differences between nutrients. Competition between bacteria and phytoplankton for depleted DIN could have contributed to the phytoplankton bloom termination.

Heterotrophic bacterial utilization of nitrogenous and nonnitrogenous substrates, determined from ammonia and oxygen fluxes - Rubina M. N. V. Rodrigues; Peter J. le B. Williams (Limnology and Oceanography, 2001)
We describe a simple procedure to allow the broad nature of the organic substrates used for planktonic bacterial growth to be determined. The method analyzes the coupled oxygen and ammonia fluxes in terms of the relative proportions of nitrogenous and nonnitrogenous substrates assimilated by the microheterotrophs. The model uses a stoichiometric equation that requires the knowledge of the respiratory quotient, substrate C/N ratio, cell C/N quota, and bacterial carbon growth yield and the assumption that nitrification was not occurring. We discuss the uncertainties associated with the attribution of values for these constants and illustrate the use and limitations of the approach in the interpretation of field observations on bacterioplankton metabolism in a temperate coastal ecosystem. With the exception of a single observation, we were able to interpret the data using the proposed model. Our findings are that during the spring bloom, nitrogenous substrates made up 40–80% of the total, falling to

Plant-soil interactions in multistrata agroforestry in the humid tropicsa - G. Schroth; J. Lehmann; M. R. L. Rodrigues; E. Barros; J. L. V. Macêdo (Agroforestry Systems, 2001)

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

Varying responses of herbivorous and invertebrate-feeding fishes to macroalgal reduction on a coral reef - T. R. McClanahan; V. Hendrick; M. J. Rodrigues; N. V. C. Polunin (Coral Reefs, 1999)

Sediment chemistry — Infaunal community structure in a southern European estuary related to solid-phase Microtox® toxicity testing - V. Quintino; A. M. Picado; A. M. Rodrigues; E. Mendonça; M. H. Costa; M. Bordalo Costa; P. Lindgaard-Jørgensen; T. H. Pearson (Aquatic Ecology, 1995)

Effect of selenium supplementation on some blood biochemical parameters in male rats - A. M. Viegas Crespo; M. J. Lança; S. Vasconcelos; V. Andrade; H. Rodrigues; M. C. Santos (Biological Trace Element Research, 1995)

The effect of age and selenium on some biochemical parameters in rat liver - M. C. Santos; H. Rodrigues; S. Vasconcelos; V. Andrade; M. J. Lança; A. M. Viegas Crespo (Biological Trace Element Research, 1995)